2007
DOI: 10.1007/s10565-007-9017-y
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid rutin induces astrocyte and microglia activation and regulates TNF-alpha and NO release in primary glial cell cultures

Abstract: Astrocyte and microglia cells play an important role in the central nervous system (CNS). They react to various external aggressions by becoming reactive and releasing neurotrophic and/or neurotoxic factors. Rutin is a flavonoid found in many plants and has been shown to have some biological activities, but its direct effects on cells of the CNS have not been well studied. To investigate its potential effects on CNS glial cells, we used both astrocyte primary cultures and astrocyte/microglia mixed primary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 49 publications
(43 reference statements)
0
31
1
Order By: Relevance
“…Although flavonoids have been reported to act on glial cells, we did not observe effects in oligodendrocytes and astrocyte pools [20,33]. A specific receptor for flavonoids has not been identified yet.…”
Section: Discussioncontrasting
confidence: 77%
“…Although flavonoids have been reported to act on glial cells, we did not observe effects in oligodendrocytes and astrocyte pools [20,33]. A specific receptor for flavonoids has not been identified yet.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies of our group and others revealed that glial cells might be targeted by different flavonoids, leading to modulation of the inflammatory response (Sharma et al, 2007), proliferation (Kobayakawa et al, 2004), and morphology (Silva et al, 2008). However, the effects of casticin on astrocytes, as well as the role of astrocytes as mediators of flavonoid effects on neuronal morphogenesis, have not been addressed before.…”
Section: Effect Of Casticin On Astrocytesmentioning
confidence: 93%
“…These data, together with the possibility that these cells might be a target for flavonoids (Silva et al, 2008), led us to investigate whether casticin might act on neurons through astrocytes.…”
Section: Astrocytes Are Mediators Of Casticin In Neuronal Morphogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Naringenin, a member of the flavanone family, exhibits high permeability as measured by in vitro and in situ BBB models, suggesting that this family of flavonoids should afford good neuroprotection within the CNS. Nevertheless, some restriction of entry caused by efflux transporters may affect certain flavonoids, such as quercetin [101].…”
Section: Classification Structure and Actions Of Flavonoids In The Cmentioning
confidence: 99%